A Retrospective Audit on Evaluation of Acute Adverse Drug Reactions at Hameed Latif Hospital - Atiq , Ali; Ahmed , Muhammad; Mehmood , Asif; Raja , Mahnoor Farooq; Shafique, Ramsha; Mannan, Asim (Indus Journal of Bioscience Research, 2025)
Background: Adverse drug reactions (ADRs) are a major cause of patient morbidity and can lead to prolonged hospitalization, increased healthcare costs, and in some cases, life-threatening complications. Objective: To evaluate the incidence, patterns, severity, and documentation quality of acute adverse drug reactions reported at Hameed Latif Hospital, and to assess adherence to WHO and institutional reporting standards. Methods: This retrospective audit was conducted at Hameed Latif Hospital from Jan 2023 to Dec 2024. A total of 219 ADR forms were reviewed, all of which reported reactions occurring within 24–72 hours of drug administration. Data were extracted on patient demographics, suspected drugs, type and severity of reactions, management strategies, outcomes, and quality of documentation. Results: The incidence rate of acute ADRs was 1.90% among 11,510 hospital admissions. Females accounted for 64% of cases, and the highest frequency was observed in patients aged over 50 years. Comorbidities such as diabetes (35%) and hypertension (36%) were common among affected individuals. Antibiotics, analgesics, and iron infusions were the most frequently implicated drug classes. Most ADRs were of mild to moderate severity, but 19% required hospitalization and 3% needed ICU care. Drug discontinuation was the most common management strategy (81%), and 91% of patients achieved complete recovery. However, only 62% of forms included a formal causality assessment, and 28% were submitted beyond the recommended reporting timeframe. Conclusion: It is concluded that acute ADRs are prevalent and clinically significant, particularly among patients with comorbid conditions and those exposed to high-risk drug classes. While most cases were managed successfully, deficiencies in documentation, delayed reporting, and inconsistent use of assessment tools highlight the need for improved pharmacovigilance practices.